miR-664 negatively regulates PLP2 and promotes cell proliferation and invasion in T-cell acute lymphoblastic leukaemia - Zhu, Hong; Miao, Mei-Hua; Ji, Xue-Qiang; Xue, Jun; Shao, Xue-Jun (Biochemical and biophysical research communications, 2015)
MicroRNAs (miRNAs) play important roles in the pathogenesis of many types of cancers by negatively regulating gene expression at posttranscriptional level. However, the role of microRNAs in leukaemia, particularly T-cell acute lymphoblastic leukaemia (T-ALL), has remained elusive. Here, we identified miR-664 and its predicted target gene PLP2 were differentially expressed in T-ALL using bioinformatics methods. In T-ALL cell lines, CCK-8 proliferation assay indicated that the cell proliferation was promoted by miR-664, while miR-664 inhibitor could significantly inhibited the proliferation. Moreover, migration and invasion assay showed that overexpression of miR-664 could significantly promoted the migration and invasion of T-ALL cells, whereas miR-664 inhibitor could reduce cell migration and invasion. luciferase assays confirmed that miR-664 directly bound to the 3'untranslated region of PLP2, and western blotting showed that miR-664 suppressed the expression of PLP2 at the protein levels. This study indicated that miR-664 negatively regulates PLP2 and promotes proliferation and invasion of T-ALL cell lines. Thus, miR-664 may represent a potential therapeutic target for T-ALL intervention.